Enhancing Elementary Students' Language Development Through Speaking Skills and Interactive Teaching: A Systematic Literature Review - Wulansari, Nesty; Hardianto, Deny (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking ability is a crucial component of English language acquisition in primary education; however, its development is often hindered by suboptimal instructional methods and media. This study employs a Systematic Literature Review (SLR) to evaluate the effectiveness of various speaking instruction approaches, analyzing a total of 19 journal articles published between 2018 and 2023, sourced from reputable databases such as Semantic Scholar and ERIC. Findings indicate that interactive and technology-assisted methods—including storytelling, gamification, and role-playing—enhance students' speaking proficiency. The integration of digital platforms such as YouTube and Facebook, along with visual media (e.g., images and videos), further supports engagement and comprehension. Additionally, effective teacher-student communication fosters a conducive learning environment. Despite these advantages, several challenges persist, including technological limitations, reliance on traditional teaching approaches, and minimal parental involvement. Addressing these barriers requires an adaptive curriculum and the strategic integration of interactive technology to facilitate engaging, effective, and contextually relevant English language learning in 21st-century education.